2019
DOI: 10.3390/ijms20163987
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Versus Pro-Apoptotic Effects of Mushroom-Enriched Diets on Mitochondria in Liver Disease

Abstract: Mitochondria play a central role in non-alcoholic fatty liver disease (NAFLD) progression and in the control of cell death signalling during the progression to hepatocellular carcinoma (HCC). Associated with the metabolic syndrome, NAFLD is mostly driven by insulin-resistant white adipose tissue lipolysis that results in an increased hepatic fatty acid influx and the ectopic accumulation of fat in the liver. Upregulation of beta-oxidation as one compensatory mechanism leads to an increase in mitochondrial tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 267 publications
0
26
0
1
Order By: Relevance
“…This suggestion was aligned with those stated that the cell mediates the activation of either survival or pro-apoptotic pathways, including NF-kB, the tumor suppressor p53 and JNK in response to CP treatment. 72 Furthermore, our results showed that GLM treatment elicited modulation of inflammatory cytokines and suppression of apoptosis in CPinduced hepatotoxicity, which could be due to decreased oxidative stress-mediated apoptosis. This cross-talk between the inflammatory and apoptotic signaling is normalized by administration of GLM in daily-, EOD-and the i.p-treated groups.…”
Section: Figure 14mentioning
confidence: 61%
“…This suggestion was aligned with those stated that the cell mediates the activation of either survival or pro-apoptotic pathways, including NF-kB, the tumor suppressor p53 and JNK in response to CP treatment. 72 Furthermore, our results showed that GLM treatment elicited modulation of inflammatory cytokines and suppression of apoptosis in CPinduced hepatotoxicity, which could be due to decreased oxidative stress-mediated apoptosis. This cross-talk between the inflammatory and apoptotic signaling is normalized by administration of GLM in daily-, EOD-and the i.p-treated groups.…”
Section: Figure 14mentioning
confidence: 61%
“…[ 72 ] These multitudinous benefits may also be attributed to the abundance of other bioactive molecules that mushrooms harbor, like phenolic compounds, ergosterol, and tocopherols, among others. [ 73 ] Various animal studies have also demonstrated that consumption of mushrooms (fruiting bodies) significantly reduces obesity. [ 74,75 ] It would also be interesting to study whether the biotechnologically produced PSC used in this study may have similar, lipid‐lowering effects in the adipose tissue as seen in the liver of the OPSC group.…”
Section: Discussionmentioning
confidence: 99%
“…Many people are interested in edible mushroom fruiting bodies and their mycelia as functional foods because they are less toxic and contain bioactive compounds. Investigators have reported the antitumour [14], antimutagenicity [15], antiviral [16], and antioxidant activities [17] of mushroom fruiting bodies and mycelia. Mushroom mycelia have been investigated for their potential food applications, and they are used to create fermented foods like soybeans, bread, cheese, and alcoholic drinks [18].…”
Section: Introductionmentioning
confidence: 99%